Secrets of the Hood People (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The Qur’an was the constitution by which they worked, and they were among the memorizers of the Qur’an because of their love for it. Therefore, one of them would memorize the Qur’an by heart out of love and seek reward for the Wise Remembrance. The stories of the earliest prophets, the righteous, and other nations who had mistreated themselves and disobeyed God's rules were revealed by God in a similar way to how He revealed meanings other than those of heaven and told them that they would suffer retribution while they slept. As God Almighty said, "Do they not consider the Qur'an? The Qur'an is also open to competition, exploration, and contemplation. What must be understood, however, is familiarity with the foundations: language, reasons for revelation, decisive, similar, absolute, restricted, and narrations with the well-known. If it hadn't come from God, they would have discovered a lot of contradictions in it. Here, we are not discussing careers in interpretation, which involve academics, interpreters, and people with extensive knowledge; rather, we are discussing contemplation and contemplation in general, which interest all of us.